2016
DOI: 10.1371/journal.pone.0163311
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Receptor Expression Analyses in Neoplastic and Non-Neoplastic Canine Mammary Tissue by a Bead Based Multiplex Branched DNA Assay: A Gene Expression Study in Fresh Frozen and Formalin-Fixed, Paraffin-Embedded Samples

Abstract: Immunohistochemistry (IHC) is currently considered the method of choice for steroid hormone receptor status evaluation in human breast cancer and, therefore, it is commonly utilized for assessing canine mammary tumors. In case of low hormone receptor expression, IHC is limited and thus is complemented by molecular analyses. In the present study, a multiplex bDNA assay was evaluated as a method for hormone receptor gene expression detection in canine mammary tissues. Estrogen receptor (ESR1), progesterone recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 34 publications
3
13
0
7
Order By: Relevance
“…42 Our study, in turn, showed a significantly lower expression of the transcript in carcinomas than in adenomas and normal glands, a finding also described in the literature. 27 As expected, ESR1 transcript level corresponded to ERa protein expression. However, three of the six carcinomas that showed a score 0 for the ERa protein expressed ESR1 mRNA.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…42 Our study, in turn, showed a significantly lower expression of the transcript in carcinomas than in adenomas and normal glands, a finding also described in the literature. 27 As expected, ESR1 transcript level corresponded to ERa protein expression. However, three of the six carcinomas that showed a score 0 for the ERa protein expressed ESR1 mRNA.…”
Section: Discussionsupporting
confidence: 70%
“…Similar data concerning ERa have been reported in human breast 15 and ovarian cancers. 19 This divergence among transcript and protein levels has been attributed to the variations in the immunohistochemical assay 17,27 techniques, such as antibody clones and fixation time of the tissue. 30 However, other factors such as posttranscriptional regulation should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have found that dogs with CMC have higher levels of estrogens in the blood, except in IMC, where the serum estrogens levels are lower than in dogs with other malignant mammary tumors ( 89 , 90 ). On the other hand, ER, PR, PRL, PRL receptor, and GH receptor have been found to be downregulated in malignant mammary tumors compared to normal mammary gland ( 91 , 92 ) and benign tumors ( 92 94 ). Furthermore, lymphatic invasion, high mitotic index, large tumor size, and tumor grade are significantly associated with low ER/PR expressions.…”
Section: Adjuvant Targeted Therapiesmentioning
confidence: 99%
“…Hormone receptor expression is significantly reduced in malignant breast tumours, compared to non-neoplastic tissue and benign neoplasia. Among histological subtypes, minimal expression levels of estrogen receptor genes (ESR1), progesterone (PGR), and prolactin (PRLR) have been established in solid, anaplastic, and ductal cancers (Mohr et al, 2016). Canadas-Sousa et al (2019) identified genetic profiles, in particular ESR1 (rs397512133, rs397510462, rs851327560, rs397510612, rs852887655, rs852684753, rs852398698) associated with the later development of neoplasms of lactic pathology: significant tubular differentiation, and low dog-adjusted prognostic index (vet-NPI).…”
Section: Clinical and Ecological Aspects Of Biology Of Breast Neoplasmentioning
confidence: 99%